(untitled) (OverHolland, 2009)
The study of the designers and builders of architectural works is one of the central themes of architectural history. Over the last few decades, interest in this area has broadened to include not only prominent individuals but also the structure of design and building practice. In the Low Countries, the architectural historian Meischke was one of the first to perform extensive research on developments in the organization of the building profession. This line of research has made great advances in the past fifteen years with the publication of several noteworthy doctoral theses. Kolman’s 1993 thesis investigates the building industry in Kampen from the fifteenth to the midseventeenth century, and Steenmeijer’s 2001 thesis on Arent van ’sGravensande deals in passing with municipal construction companies in Leiden and The Hague. Other researchers have opted for a thematic approach, dealing with multiple cities at once. In a 2001 thesis, Van Tussenbroek investigates the Van Neurenberg family’s trade in stone in the Maas river valley and the cities of Holland in the sixteenth and seventeenth centuries. A similarly specific topic was chosen by Gerritsen, whose 2004 thesis deals with the role of drawings in design and building practice in the seventeenthcentury Dutch Republic. At Utrecht University, Röell is currently engaged in a followup study of the same topic, focusing on the eighteenth century. The emergence of municipal construction companies in various cities in the seventeenth and eighteenth centuries is being investigated from a comparative perspective by Medema, who recently finished his research, and by Van Essen, who is soon to complete her thesis. Van Essen analyzes the development of the office of the stadsfabriek in the seventeenthcentury Dutch Republic, taking Amsterdam and Groningen as her two main case studies. Medema’s work is thematically linked to Van Essen’s, but focuses on the eighteenth century, a period when on the whole the industry shrank, necessitating reorganization and professionalization. The most recent investigation of civic building activity in Holland was carried out by Hurx and examines the major city churches that are among the first largescale works of civic architecture in Holland. Because of the scale and complexity of these issues, many of the abovementioned studies are restricted to a narrowly defined topic, period, or geographical area. There is still no general survey of the development of design and building practice in the cities of Holland over an extended period. In this article we attempt, on the basis of our own research, to sketch a few main lines of development from the fourteenth to the nineteenth century and to point out a few gaps in our current knowledge. In examining the leading public works of civic architecture, the authors aim to trace the most significant transformations through the centuries, in the belief that organizational changes can best be explained by reference to shifts in the demand for building work. The emphasis lies on church building in the fifteenth century and on the municipal building industry in later centuries, because these activities showed a high degree of organization. The article will be published in two consecutive issues of OverHolland, in which various authors will discuss the periods of growth and contraction in the demand for building work, in chronological order. Each of the two parts will begin with a brief introductory section presenting the periods and major themes to be examined. In part I, which covers the period from the fourteenth to the sixteenth century, Hurx begins with the boom in the construction of city churches in the fourteenth and fifteenth centuries. Van Essen then describes how city authorities assumed increasing responsibility for public works in the fifteenth and particularly the sixteenth century. Part II will begin with an examination of the massive increase in the scale of building work in the seventeenth century, stemming from the explosive growth of a number of cities. In this section, Van Essen will describe the development of the office of the stadsfabriek into a largescale municipal construction company. In the second section of part II, Medema will discuss the reorganization of the building sector in the eighteenth century as a result of economic decline. We assume that fluctuations in the demand for building work not only had a crucial impact on the makeup of the building industry as a whole, but also had consequences for the specialists at the top of that industry. The base of the building trade remained largely unchanged until the eighteenth century; in the cities, it was composed largely of small, autonomous workshops each devoted to a single craft, and each consisting of a single master craftsman with a small number of assistants and apprentices. Even in times of economic recession, there was enough demand for labour to ensure the continued existence of this group of artisans. In many cities in Holland, they formed guilds, which were founded between the fourteenth and the seventeenth century. The development and organization of these guilds will not be discussed in detail here, because they did not have a decisive influence on public works. When the church and the city authorities commissioned architectural works, they were not generally subject to guild regulations. The top of the industry was formed in part by officials responsible for the administrative and financial aspects of building projects. They often coordinated building projects on behalf of the commissioning body and made decisions about daytoday expenditure (usually up to a specified maximum). But they frequently lacked the expertise to manage the technical and aesthetic aspects of such projects, and specialized professionals were engaged for this purpose. Such experts were relatively vulnerable to shifts in the supply of building work, because they were needed only for complex projects. We contend that the larger the amount of building work requiring special technical, logistical, or aesthetic expertise, the more pronounced the division of labour, and the larger the organizational distance between these experts and the labourers. The remainder of this article investigates this proposed relationship in greater depth. Because of the dynamics in the hierarchical organization of the building trade, it is sometimes difficult to determine the precise composition of the top level. The role of experts in the building process could vary from project to project, and the terminology used at the time can be misleading. Given that these potential sources of confusion are encountered throughout the period in question, a brief discussion of them is advisable. In the fifteenth and early sixteenthcentury Low Countries, the individual who supervised the building process on behalf of the commissioning party was generally referred to as the werkmeester or something similar. But this word also had other uses; in particular, it could serve as a generic term for any expert practitioner of a craft or trade. In fifteenthcentury Latin sources, several terms are used to denote the werkmeester, namely archilathomus, archilapicida, and architectus. The prefix archi comes from the Greek αρχι (‘uppermost’) or from αρχω (‘to lead’), while lathomus and lapicida mean stonemason and tectus is derived from the Greek word for craftsman or carpenter, τηκτων. This etymology reflects the original, leadership role of the architectus, who supervised a variety of activities ranging from drawing up building plans (in the broadest sense) to managing workers through written and oral instructions, drawings and templates. The architectus might also be responsible for the quality of the building materials and the logistics of transporting them to the site. In the course of the sixteenth century, the nativized word architect came into widespread use. Until the eighteenth century, it was primarily a term for the individual who supervised a building project and was used only in a secondary sense for the individual who produced the designs. Throughout this period, the Dutch word architect had more than one meaning, and primary sources sometimes use the term in ways which have nothing to do with architectural design. This historical Dutch term often does not correspond to its modern English and Dutch cognate, architect, which refers primarily to the designer of a structure. Throughout the remainder of this article, the word architect is used in the historical sense of the organizer and leader of a building project – who may or may not also have been the designer. Individuals who did no more than contribute design drawings will be referred to in more neutra